Non-glycosylated G protein with CpG ODN provides robust protection against respiratory syncytial virus without inducing eosinophilia - Eigo Kawahara; Eigo Kawahara; Takehiko Shibata; Toshiro Hirai; Toshiro Hirai; Toshiro Hirai; Toshiro Hirai; Yasuo Yoshioka; Yasuo Yoshioka; Yasuo Yoshioka; Yasuo Yoshioka; Yasuo Yoshioka; et al. (Frontiers in Immunology, 2023)
IntroductionRespiratory syncytial virus (RSV) vaccines targeting the fusion glycoprotein (F protein) are highly effective clinically in preventing RSV challenges. The attachment glycoprotein (G protein) is a potentially effective vaccine antigen candidate, as it is important for cell adhesion during infection. However, vaccine-associated enhanced diseases in mice, such as eosinophilic lung inflammation following RSV challenge, are a concern with G protein vaccines. This study aimed to design an effective G protein vaccine with enhanced safety and efficacy by evaluating the efficacy and adverse reactions of vaccines composed of different recombinant G proteins and adjuvants in mice.MethodsMice were subcutaneously immunized with glycosylated G protein expressed in mammalian cells (mG), non-glycosylated G protein expressed in Escherichia coli (eG), or F protein with or without aluminum salts (alum), CpG oligodeoxynucleotide (CpG ODN), or AddaVax. After vaccination, the levels of G-specific antibody and T-cell responses were measured. The immunized mice were challenged with RSV and examined for the viral load in the lungs and nasal turbinates, lung-infiltrating cells, and lung pathology.ResultsmG with any adjuvant was ineffective at inducing G-specific antibodies and had difficulty achieving both protection against RSV challenge and eosinophilia suppression. In particular, mG+CpG ODN induced G-specific T helper 1 (Th1) cells but only a few G-specific antibodies and did not protect against RSV challenge. However, eG+CpG ODN induced high levels of G-specific antibodies and Th1 cells and protected against RSV challenge without inducing pulmonary inflammation. Moreover, the combination vaccine of eG+F+CpG ODN showed greater protection against upper respiratory tract RSV challenge than using each single antigen vaccine alone.DiscussionThese results indicate that the efficacy of recombinant G protein vaccines can be enhanced without inducing adverse reactions by using appropriate antigens and adjuvants, and their efficacy is further enhanced in the combination vaccine with F protein. These data provide valuable information for the clinical application of G protein vaccines.